STUDI PEMBUATAN TEH CELUP DARI DAUN KOPI ROBUSTA (Coffea canephora) (KAJIAN VARIASI SUHU PENYANGRAIAN DAUN UMUR DAUN) - Hanif Dewiansyah; Rizky Muliani Dwi Ujianti; Rini Umiyati; Fafa Nurdyansyah (Pro Food, 2022)
The pruned coffee leaves are usually thrown away so that further utilization is needed because in addition to having a fairly high tannin content, they also have a taste that is no less delicious than coffee beans. However, there are not many uses that produce innovative products from coffee leaves. One of the efforts to use coffee leaves is to make coffee leaf tea bags. The purpose of this study was to study the effect of coffee leaf age and different roasting temperatures on the chemical and sensory properties of coffee leaf powder and teabags steeped. This study used a factorial completely randomized design with 2 factors, namely (study of variations in roasting temperature of 40°C, 60°C and age of robusta leaves). Analysis of the data used is ANOVA at a significance level of 5%. This research was carried out by picking, sorting, withering for ±3 hours, washing, size reduction, drying at 45°C for ±3 hours, roasting for ±15 minutes, milling, packaging for dye bags, brewing for ±5 minutes, and analysis. The results obtained from the organoleptic test showed that the results of powdered and steeped teabags for RT coffee leaves at a temperature of 60°C were preferred by panelists because the overall aspects resembled tea drinks in general, with quality criteria in accordance with SNI, namely water content 9.40%, water content Ash 7.30%, Total phenol 5.09%, antioxidant activity 38.46%.